Building a modern economic system: Basic framework, key issues, and theoretical innovation - Zhibiao Liu (China Political Economy (CPE), 2019)
Purpose The construction of a modern economic system is a symbolic and strategic choice for large developing economies on the path toward high-quality economic development. The paper aims to discuss this issue. Design/methodology/approach The overall framework aims to adhere to "One Policy and One Mainline" to build an innovation-driven, synergistic industrial system and a "with three-qualities" economic system (with efficient market mechanisms, energetic micro-agents and appropriate macroeconomic regulation). Findings The strengthening of the real economy and construction of a modern industrial system constitute the material basis for supporting this system and framework. As major decision making and theoretical innovation in empirical practice, building a modern economic system can also contribute substantially toward developing the applied economic theory of socialism with Chinese characteristics. Originality/value Building a modern economic system in China necessitates, without exception, the construction of various subsystems encompassing industrial, market, distribution, regional development, green development, open and economic institutional aspects.
Keywords: 330; Economic theory innovation; High-quality development; Modern economic system; Real economy